Paul and his theology - Porter, Stanley E., 1956- (Leiden ; Boston : Brill, 2006)
Does Paul have a theology? If so, what is it, or rather, what is it on various topics that he and the early Church confronted? This volume moves beyond the traditional discussion of whether Paul had a center to his theology to raise questions regarding his perspective on a number of important theological issues. These issues include his gentile mission, the concepts of faith, grace, and the law, reconciliation, the temple, eschatology, miracles, gender, and Paul's trinitarian tendencies. This collection of essays addresses topics of current interest in the study of Paul's theology, not to arrive at the center of his thought, but to understand what factors helped to center his thinking on a variety of important theological concerns.
Is there a center to Paul's theology? / Stanley E. Porter -- The scriptural foundations for Paul's mission to the Gentiles / Arland J. Hultgren -- Paul's understanding of faith as participation / David M. Hay -- Paul, theologian of electing grace / James R. Harrison -- Paul, the law and the Spirit / Colin G. Kruse -- Paul's concept of reconciliation, twice more / Stanley E. Porter -- Color outside the lines : rethinking how to interpret Paul's letters / Randall K.J. Tan -- The Spirit and the temple in Paul's letters to the Corinthians / John R. Levison -- Eschatology in Philippians / Heinz Giesen -- Neither hierarchicalist nor egalitarian : gender roles in Paul / Craig L. Blomberg -- Was Paul a Trinitarian? : a look at Romans 8 / Ron C. Fay -- Pauline pneumatology and the question of Trinitarian presuppositions / Andrew K. Gabriel -- Paul the exorcist and healer / Craig A. Evans -- The interpretation of the Letter to the Romans in Melanchthon's Loci communes from 1521 / René Kieffer -- Adolf Deissmann, a reappraisal of his work, especially his views on the mysticism of Paul / Jan de Villiers.
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Bible. -- Theology; Bible. -- Criticism, interpretation, etc; Bible -- Théologie.; Bible -- Critique, interprétation, etc; Bible. -- Théologie.; Bible; RELIGION -- Biblical Studies -- New Testament; RELIGION -- Biblical Studies -- Paul's Letters; Theology; Brieven van Paulus; Nieuwtestamentische theologie; Criticism, interpretation, etc